Strategi Komunikasi Dalam Meningkatkan Citra Merek Komik Jopa Jopi Melalui Instagram - Rio Juliantoni; Shulhuly Ashfahani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This research aims to analyze the communication strategies used by Jogja Painting in enhancing the brand image of the Jopa Jopi comic. Jogja Painting is a successful art and creative company that has created the popular Jopa Jopi comic, attracting numerous readers. However, the brand image of this comic still needs improvement to gain broader recognition and acceptance. The research method employed is a descriptive qualitative approach. Data was obtained through in-depth interviews with Jogja Painting's management and observations of their communication activities. The findings reveal that Jogja Painting's communication strategies are not yet optimal due to incomplete implementation. The various stages of the communication strategies have not been fully executed, resulting in minimal changes to the brand image and limited reach to a wider audience. Obstacles include difficulties in generating story ideas, monotonous content that fails to engage readers, and visually unappealing aspects of the Jopa Jopi comic. To enhance the brand image, Jogja Painting needs to improve its communication strategies and address these obstacles, enabling the Jopa Jopi comic to gain greater popularity among a wider audience. .